Bibliometric analysis of the effects of mental fatigue on athletic performance from 2001 to 2021 - Chen, Xiao-Xin; Ji, Zhi-Guang; Wang, Yi; Xu, Jing; Wang, Li-Yan; Wang, Hong-Biao (Frontiers in Psychology, 2023)
Aims To explore the research hot topics and main contents in the field of the influence of mental fatigue on athletic performance, and to provide new ideas and directions for future research in this field. Methods Using CiteSpace and VOSviewer visualization tool software core collection of Web of Science database to TS = (“mental fatigue” OR “mental exertion” OR “cognitive fatigue” OR “Cognitive exertion” OR “mental exhaustion” OR “mental tiredness”) AND (“athletic performance” OR “technical skill*” OR “Skill*” OR “technique” OR “decision making” OR “performance”) AND (“Humans”) searched for the influence of mental fatigue on athletic performance from 2001 to 2021 to conduct visual analysis. Research hot topics were analyzed from the aspects of high-impact countries/regions, institutions, authors, high-frequency keywords, and mutation terms. Results A total of 658 publications were identified finally, and there has been an increasing trend in the annual number of publications, with the United States ranking first in the number of publications and influence. Future research will focus on promoting the application of EEG technology as an objective indicator for assessing mental fatigue, exploring effective methods and measures for pharmacological or non-pharmacological interventions against fatigue, and focusing on the effects of mental fatigue on endurance performance, technical skills, and sports-related decision-making. Conclusion The results of the present study help us understand the status of the mental fatigue and athletic performance field and its recent developments.